Bibliometric Analysis on Sustainable Development Goals (SDGs): Decent Work and Economic Growth - Asriani, Asriani (LPPPIPublishing, 2024)
This research carries out a bibliometric analysis of scientific literature related to the Sustainable Development Goals (SDGs), especially SDGS 8 (eight) which focuses on decent work and economic growth. The aim of this research is to measure and analyze various aspects of scientific publications in order to understand research trends, collaboration between researchers, and the impact of studies related to SDGS 8 (eight). Through this analysis, this research identifies research patterns, knowledge gaps, and opportunities for further research. Additionally, this research assesses the impact and contribution of various journals, institutions, and individual researchers in advancing understanding of SDGS 8 ( eight ). The research results demonstrate the dynamics and interconnectivity within the global research community, and highlight the most influential publications and authors. This research also explores how regional and national contexts influence research on SDGS 8 (eight), providing more relevant and specific recommendations for the implementation of SDGS 8 (eight) in various countries. Thus, this research provides an in-depth and comprehensive insight into the literature relating to decent work and economic growth, as well as its contribution to the global understanding of SDGS 8 (eight).